PELATIHAN PENGENDALIAN FAKTOR RISIKO HIPERTENSI PADA KADER DI DESA BANDUNG KECAMATAN DIWEK KABUPATEN JOMBANG - siswati siswati; desy siswi anjar sari; Fitri Firranda Nurmalisyah (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Hypertension continues to be a concern of the health world, because this disease has unique characteristics. Efforts to prevent and control hypertension require cross-sectoral and cross-programme collaboration, one approach is education and training to control hypertension risk factors. This community service makes health cadres the target of activities using the method of controlling hypertension risk factors, and is carried out in Bandung Village, Diwek District, Jombang Regency. Bandung village is the area with the most hypertension sufferers in the working area of Cukir Health Center. Community service activities are carried out in stages, first measuring the knowledge of cadres with a pretest, followed by counseling, then training on anthropometric measurements, and ending with a posttest. The result of increasing knowledge and skills of cadres after being given training